2008
DOI: 10.3791/772
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Epidermal Neural Crest Stem Cell (EPI-NCSC) Cultures

Abstract: EPI-NCSC are remnants of the embryonic neural crest in an adult location, the bulge of hair follicles. They are multipotent stem cells that have the physiological property to generate a wide array of differentiated cell types, including neurons, nerve supporting cells, smooth muscle cells, bone/cartilage cells and melanocytes. EPI-NCSC are easily accessible in the hairy skin and can be isolated as a highly pure population of stem cells. This video provides a detailed protocol for preparing mouse EPI-NCSC cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Adult neural crest-derived cells have been shown to retain stem cell properties [ 33 ]. Studies have consistently demonstrated that such neural crest stem cell (NCSC) populations often mimic transcription expression profiles of both embryonic stem cells and early neural crest cells [ 34 - 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adult neural crest-derived cells have been shown to retain stem cell properties [ 33 ]. Studies have consistently demonstrated that such neural crest stem cell (NCSC) populations often mimic transcription expression profiles of both embryonic stem cells and early neural crest cells [ 34 - 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whisker follicle stem cell culture, substratum coating and immunocytochemistry Whisker follicle stem cells were cultured using an adaptation of published methods (Sieber-Blum and Hu, 2008). In brief, the dissected whisker fragment containing the stem cells was placed onto a plastic dish or coverslip coated previously with extracellular matrix (see below) with a small amount of medium and allowed to adhere for 1-2 hours.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…It has been proposed that the CD34-positive stem cells migrate along the glassy membrane of the outer root sheath to the dermal papilla, where they contribute to the development of the whisker shaft (Amoh et al, 2010). These cells can be isolated and studied in culture by explanting the whisker bulge and associated trabeculae (Sieber-Blum et al, 2004;Sieber-Blum and Hu, 2008), and have the potential to differentiate into neurons and nonneuronal cells in vitro (Sieber-Blum et al, 2004;Wong et al, 2006;Amoh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the adult organism, progenitor cells of the neural crest are found in many types of tissues, including skin [ 10 , 11 ], dorsal root ganglia [ 12 ], adrenal medulla [ 13 ], bone marrow [ 14 ], and a number of other tissues [ 15 ]. It has been shown that adult neural crest-derived cells retain the properties of stem cells [ 16 ]. Several studies have demonstrated that such neural crest stem cell populations often mimic the transcriptional expression profiles of both embryonic stem cells and neural crest progenitor cells [ 17 ].…”
Section: Origin Of Neuroblastomamentioning
confidence: 99%